Patellofemoral Instability in the Pediatric and Adolescent Population: From Causes to Treatments - Anthony Ricciuti; Katelyn Colosi; Kevin Fitzsimmons; Matthew Brown (Children, 2024)
Background: Patella instability is one of the most common knee injuries in the adolescent patient. There are several pathoanatomic risk factors which should be assessed via several modalities, including X-rays, magnetic resonance imaging (MRI), or even CT scan. Objectives: We intend to review these risk factors along with the nonsurgical and surgical techniques used to prevent recurrent dislocations. Methods: We completed an extensive review of the recent literature concerning pediatric and adolescent patellar dislocation and subsequent treatment modalities. Results: We review in detail the risk factors such as patella alta, trochlear dysplasia, lateralization of the tibial tubercle or medialization of the trochlear groove (increased tibial tubercle to trochlear groove (TT–TG) distance), lower limb malalignment, excessive femoral anteversion and/or tibial torsion, and hyperlaxity. There are classification systems for dislocators, and a natural progression of instability that patients often proceed through. Only after a patient has continued to dislocate after bracing and physical therapy is surgical treatment considered. Surgical techniques vary, with the workhorse being the medial patellofemoral ligament (MPFL) reconstruction. However, there are a variety of other techniques which add onto this procedure to address other anatomic risk factors. These include the tibial tubercle osteotomy to address a large TT–TG distance or trochleoplasty to address the lack of a trochlear groove. Conclusions: Nonsurgical and surgical treatments for patella dislocators are tailored to the pathoanatomic risk factors in each patient.